Ḥilm sebagai Faktor Mediasi dalam Pengembangan Kewirausahaan Sosial Berbasis Kelautan di Kalangan Nelayan - Aziza, Andi Rezky Nur; Razak, Syaparuddin; Hamzah, Aksi; Karyono, Otong (Moneta: Jurnal Manajemen & Keuangan Syariah, 2026)
This study examines the mediating effect of ḥilm on marine resource-based social entrepreneurship among fisher communities by integrating Resilience Theory, Stakeholder Theory, and the Triple Bottom Line (TBL) framework. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (SEM-PLS), with data collected from 240 fishermen in South Sulawesi, Indonesia, through a structured questionnaire. The findings reveal that community engagement significantly influences product innovation, which in turn strengthens the coastal economy. A robust coastal economy not only directly enhances social entrepreneurship but also positively affects government support and the internalization of ḥilm. Furthermore, ḥilm, the coastal economy, and government support are found to play significant mediating roles in the structural model. The results indicate that social entrepreneurship is shaped through an integrated process involving social participation, economic development, institutional support, and ethical values. Theoretically, this study contributes by incorporating ḥilm as an ethical mediating construct, offering a more holistic understanding of sustainable entrepreneurship in coastal contexts. Practically, the findings provide insights for policymakers to strengthen community participation, promote innovation, and enhance local economic capacity in line with social welfare and sustainability.